Antibiotic stewardship program in Pakistan: a multicenter qualitative study exploring medical doctors’ knowledge, perception and practices - Atif, Muhammad; Ihsan, Beenish; Malik, Iram; Ahmad, Nafees; Saleem, Zikria; Sehar, Azka; Babar, Zaheer-ud-Din (BMC infectious diseases, 2021)
Background The emerging threat of antibiotic resistance is growing exponentially and antibiotic stewardship programs are cornerstone to fight against this global threat. The study aimed to explore the knowledge, perspectives and practices of physicians regarding various aspects of antibiotic stewardship program including antibiotic stewardship activities, rational use of antibiotics, antibiotic resistance, prescribing practices and factors associated with these practices. Methods In this qualitative study, a total of 17 semi-structured, in-depth interviews with doctors of three tertiary care public sector hospitals in Bahawalpur and Rahim Yar Khan were conducted. The convenient sampling method was adopted to collect the data and the saturation point criterion was applied to determine the sample size. Thematic analysis approach was used to draw conclusions from the data. Results The analysis of data yielded five themes, 12 subthemes and 26 categories. The themes included, (i) perception about antibiotic use and antibiotic stewardship, (ii) antibiotic prescription practices, (iii) antibiotic resistance, (iv) limited strategies adopted by hospital administration to ensure quality and safe distribution of antibiotics, (v) implementation of antibiotic stewardship program: barriers, suggestion and future benefits. Doctors had misconceptions about the rational use of antibiotics. The perception regarding antibiotic stewardship programs was poor. Moreover, very few activities related to ASP existed. The participants gave many suggestions for successful implementation of ASP in order to reduce the burden of antibiotic resistance, including development of guidelines for the use of antibiotics, strict legislation regarding use of antibiotics, active participation of healthcare professionals and awareness program among general public about the use of antibiotics. Conclusion This study concluded that poor knowledge of doctors regarding ASP, non-existence of antibiogram of hospital and lack of rules for the safe use of antibiotics were the main driving factors associated with irrational antibiotic prescription practices and development of AR.